Tinjauan Ekonomi Islam terhadap Sistem Bagi Hasil Pertanian Mengunakan Akad Muzara’ah (Studi Muara Lintang Kecamatan Pendopo Barat Kabupaten Empat Lawang) - Ruliniati, Ruliniati; Isnaini, Desi; Pramadeka, Katra (Universitas Batanghari Jambi, 2024)
The aim of this research is to analyze the agricultural production sharing system using a muzara'ah agreement in Muara Lintang, Pendopo Barat District, Empat Lawang Regency from an Islamic economic perspective. Testing was carried out using subjective methods and data collection using purposive testing methods. The sample determination in this research was a purposive test. The research results found that there are still disparities with sharia financial standards which cause one party to feel disadvantaged and the need for candor at the beginning of understanding.